Principle of Good Faith in Peace Agreements via Mediation - Jasmaniar, Jasmaniar; Nurhaedah, Nurhaedah (Journal of Law, Politic and Humanities, 2024)
Many people have selected mediation as a dispute resolution procedure to get the best agreement and solution. However, it is not uncommon for parties to fail to consistently implement an agreement reached through mediation. The purpose of this article is to examine the essence of peace agreements reached through mediation, as well as the importance of the principle of good faith as a form of protection for the parties involved in such agreements. This is normative research that takes both a statutory and conceptual approach. The exploration of data in the form of primary and secondary legal materials was carried out through a literature review and descriptive-qualitative analysis. The analytical results reveal that the mediation process, which concludes with a peace agreement, represents the end of a dispute based on the ideals of benefit and justice. On that premise, its execution must be based on the principle of good faith to provide legal protection to the parties, whether mediation takes place in or out of court. Good faith in implementing a peace agreement is interpreted as an attitude that develops within the parties in dispute to carry out their commitments as a moral obligation to obey and accomplish things that have been agreed upon voluntarily.